Cover Image. Issue 2 (1st July 2019) - Unknown
Abstract : Cover Illustrations: From top‐left Sarracenia purpurea is a carnivorous plant which consumes a wide diversity of insect prey. Photo Credit: M. Brock Fenton Ficedula hypoleuca is a sub‐Saharan migrant that only uses the lowland woodlands of south Spain as stopover sites during their autumn migration, which confines their seed dispersal services to the early fruiting period of Pistacia lentiscus shrubs Photo Credit: Miguel Montoro Researcher Janne Koskinen collecting samples for a metabarcoding‐based analysis of arthropods, fungal associates and bacteria inhabiting mushroom fruiting bodies. A novel method presented by Koskinen et al. opens up entirely new possibilities for investigating the structure of these highly diverse assemblages inhabiting ephemeral fruiting bodies of forest fungi, many of which constitute an important resource also for humans. Photo Credit: Tommi Nyman An Oak Processionary Moth. Larval group resting on the trunk of an oak tree. This invasive species is subject to an intensive monitoring and control program in the UK. Photo Credit: James Kitson The bat, Glossophaga soricina, holds a unique keystone position in a Neotropical food web. Photo Credit: El Clare Network analysis of co‐occurring AOA, AOB, Nitrospira and Nitrobacter OTUs based on Pearson correlations (r). Complete network of all AO and NOB OTUs with degree >0. Node size is proportional to node degree, while connections between each node indicate significant positive correlations above the set threshold (p < 0.01, r = 0.64). The shape and color of the nodes denote the functional group and lineage, respectively, of each OTU, while the numbers indicate membership of co‐occurring OTUs to distinct community modules. Photo Credit: Christopher M. Jones A Killer Whale breaks the water. Photo Credit: Andy Foote Nymph of the feather mite Trouessartia sialiae from the Eastern Bluebird Sialin sialrs showing a gut full of fungal spores. Photo Credit: Heather Proctor An adult Royle's Pika in Western Himalaya. Photo Credit: Sabuj Bhattacharyya The head of a European brown shrimp. A red sediment grain can be seen. Sediment particles can at times be ingested during foraging, but it remains unclear whether this behavior is intentional. Photo Credit: Andjin Siegenthaler